Análisis del Proceso de Recuperación de la Cartera Vencida de la Cooperativa de Ahorro y Crédito San José - Agencia Ventanas - Cedeño Álava, Lissette Del Carmen (2019)
The credit union is a private financial entity, over the years this cooperative has been attracting a number of members thanks to the services it provides, one of its main characteristics is to offer loans to its members being this object of study Over time, an overdue portfolio has been credited which has proved very difficult for the advisors to recover it, the entity does not have a collection department so the advisors are responsible for visiting and notifying the partner from the first expired day The member has three months to approach the cooperative and talk to their advisor and try to reach a payment agreement, if this happens to the legal part where the judge is responsible for establishing the payment order